APPLICATION OF ISLAMIC MODES FOR MICROFINANCE IN SUDAN: A CASE STUDY OF RAHAD SCHEME - B, ELGALI M.; B, Medani M. (Gezira Journal of Economic and Social Sciences; مجلد 8 عدد 1 (2017), 2017)
Microfinance has become one of the most important mechanisms to fight poverty and economic development in the world. Sudan like other developing countries is depending on microfinance to achieve poverty alleviation and economic development. The Central Bank of Sudan has adopted microfinance programs since it is one of the appropriate mechanisms that help banks to perform their social and economic role. The idea of solidarity groups (SGs) started in Bangladesh as a solution of the warranty problem that cannot secured by small farmers. In Sudan solidarity groups are primarily introduced by the Agricultural Bank of Sudan (Fau branch) to help small farmers in the Rahad agricultural scheme who lack the sufficient guarantee to a quire loans needed to fulfill their agricultural production obligations. The aim of this paper has two folds, first to outline microfinance environment and policies of Sudan under Islamic modes, second synthesize empirical study on the case of Rahad scheme as an example for microfinance with Islamic modes to identify socioeconomic factors affecting farmer's decision to join solidarity groups. The study used secondary data to review the general environment of finance through Islamic forms in Sudan, for the case under study, a primary data were collected using structured questionnaire, a sample of 120 farmers (60 farmers joined solidarity group and 60 of self-financed farmers) were selected randomly from the scheme. A binary logistic regression model ( Logit ) was used to estimate the correlation between the dependent variable of joining of the solidarity groups, and independents variables namely, educational level, farm location, machinery possession, marital status, land ownership, animal's ownership, risk exposure and financial ability. A paired samples (T) test used to examine and estimate the difference between two paired samples means of costs and returns. The reviewed policies of Islamic microfinance modes in Sudan showed a positive environment for credit including devoting 12 percent of the total investment portfolio of each bank to microfinance credit, in addition to introducing guarantee services via the insurance companies, and suitable repayment period with low interest. The empirical results of the Logit regression showed that four variables were statistically significant in affecting the farmers’ decision of joining SGs namely are educational level, machinery ownership, financial ability and the type of land tenure. While the factors of farm location, risk exposure, and animal ownership are not significant. The paired samples (T) test used to examine and estimate the difference between two paired samples means (solidarity group and self-financed), the results showed that there are no significant differences between the means of cost and returns for the two groups, which indicate that the bank finance has no financial burden on the SGs farmers. The study recommends generalization of the solidarity group's finance in the irrigated sector of the Sudan.